(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Describe the parameters influencing the depth of the laser marking of textile products. Experimental results are presented to determine the quality of cuts on felt surfaces of different colors at specific parameters - power and speed. Approximately 100 extras were made on two materials with a change in laser power and speed. As a result, the optimal results for cutting and marking a felt are shown.